Association of cancer awareness levels with the risk of cancer in rural China: A population‐based cohort study. Issue 20 (11th August 2020) - Li, He; Zeng, Hongmei; Zheng, Rongshou; Zou, Xiaonong; Cao, Maomao; Sun, Dianqin; Zhou, Jinyi; Luo, Pengfei; Jia, Shangchun; Zha, Zhenqiu; Wang, Jialin; Ma, Hengmin; et al.
Abstract : Background: Evidence of the effects of cancer prevention knowledge on the risk of developing cancer remains scarce. The objective of this study was to prospectively examine the association of cancer prevention awareness levels with cancer risk in a population‐based cancer screening cohort in China. Methods: This prospective cohort study included 164, 341 participants aged 40 to 69 years with no history of cancer and with available information on cancer prevention core knowledge in the Esophageal, Stomach, and Liver Cancer Screening Program. Participants were recruited from 18 rural regions across 4 provinces in China from 2007 to 2014 and were followed until December 31, 2015. The core knowledge of cancer prevention content included 9 items, with a total score ranging from 0 to 100. Cox proportional hazards regression models and restricted cubic spline analysis were used to estimate hazard ratios and 95% CIs. Results: High cancer prevention knowledge scores were inversely associated with the overall risk of cancer (group 4 vs group 1: hazard ratio, 0.669; 95% CI, 0.576‐0.776). Subgroup analysis showed that this inverse association could be observed in women, participants with lower educational or income levels, and those without a family history of cancer. Restricted cubic spline analysis exhibited a nonlinear (L‐shaped) relation between cancer knowledge scores and cancer risk (overall P < .0001; nonlinear P = .0141). Conclusions: The main finding of this prospective study was that higher levels of cancer prevention awareness could be associated with a relative reduction in the risk of developing cancer. Abstract : Higher awareness levels regarding cancer prevention could be associated with a relative reduction in cancer development. Knowledge remains as a modifiable factor to reduce cancer occurrence and enhance the general population's cancer prevention knowledge, and increasing awareness is a crucial part in cancer prevention and control.